2009
DOI: 10.1080/15320380903085683
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Metals in Soils and Pore Water at Three U.S. Military Training Facilities

Abstract: Small arms firing ranges at military training facilities can have enormous heavy metal burdens (percent level) in soils.Currently there are few published works that quantify the metal content of soils and waters at military installations or speculate on the potential for migration of these contaminants into groundwater. This article documents metals in soils and waters at nine small arms training ranges at three military installations in the U.S. Soil samples were collected from the surface and shallow subsurf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The analysis also revealed that the percentage of Sb from the bullets (1-5% Sb, 95-99% Pb) is conserved in the soil profiles of all three sites with Sb percentages of 1 to 5.2% calculated as 100 × Sb/(Sb + Pb). This result is similar to previously found ratios in shooting range soils [12,50]. Compared to the surface concentrations, the decreasing Sb and Pb concentrations with increasing depth in the soils at Sites B and C indicate that both elements are strongly bound in the OM-rich topsoil and little leached down the soil profile.…”
Section: Total Sb Concentrations In the Shooting Range Soilssupporting
confidence: 80%
See 1 more Smart Citation
“…The analysis also revealed that the percentage of Sb from the bullets (1-5% Sb, 95-99% Pb) is conserved in the soil profiles of all three sites with Sb percentages of 1 to 5.2% calculated as 100 × Sb/(Sb + Pb). This result is similar to previously found ratios in shooting range soils [12,50]. Compared to the surface concentrations, the decreasing Sb and Pb concentrations with increasing depth in the soils at Sites B and C indicate that both elements are strongly bound in the OM-rich topsoil and little leached down the soil profile.…”
Section: Total Sb Concentrations In the Shooting Range Soilssupporting
confidence: 80%
“…For Sb, these concentrations are well above soil background values of 0.3-8.6 mg kg −1 [48]. However, they are in line with previously found concentrations of Sb in shooting range and mining sites that range up to 17,500 mg kg −1 [5,8,22,34,49,50]. It must be noted, however, that extremely small bullet residues (<100 μm) can be present in the soil [4].…”
Section: Total Sb Concentrations In the Shooting Range Soilssupporting
confidence: 65%
“…[1] As a consequence, it is also increasingly released into the environment, potentially leading to soil contamination of more than several thousand milligrams per kilogram in places where it is mined, used and disposed of. [2][3][4] A major source of Sb input into the environment are shooting activities, as lead bullets contain ,2 to 5 % of metallic Sb as a hardener. [1,5] In Switzerland, for example, 10 to 25 tonnes (,10-25 Mg) of Sb enter the pedosphere every year on more than 2000 shooting ranges [6,7] ; and in the United States, shooting activities deposit ,1900 tonnes (,1.9 Gg) of Sb annually [8] on ,12 000 firing ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Antimony concentrations in military and civilian shooting range soils have been reported to range from <517 to <17,500 mg kg −1 (Basunia and Landsberger, 2001;Johnson et al, 2005;Kilgour et al, 2008;Knechtenhofer et al, 2003;Mitsunobu et al, 2006;Okkenhaug et al, 2013;Spuller et al, 2007), although Scheinost et al (2006) re-ported values that approached 100,000 mg kg −1 . These excessive soil concentrations have also been reported to generate elevated Sb concentrations in pore water (Clausen and Korte, 2009;Lewis et al, 2010;Okkenhaug et al, 2013).…”
mentioning
confidence: 99%
“…Antimony is a hardening agent in lead bullets, which contain ~5% Sb (Carlin, 2000;Johnson et al, 2005;Kilgour et al, 2008). As bullets and bullet fragments corrode, Pb and Sb are released to the soil environment (Clausen and Korte, 2009;Kilgour et al, 2008). The resulting Sb concentrations can far exceed native soil levels.…”
mentioning
confidence: 99%